Fabrication of Large-Core Multicore Fiber Bragg Gratings Based on Femtosecond Laser Direct Writing Technology - Xinda Lu; Rong Zhao; Chenhui Gao; Xinyu Ye; Qiushi Qin; Hao Li; Zhixian Li; Meng Wang; Zilun Chen; Zefeng Wang (Nanomaterials)
We demonstrate the fabrication of the fiber Bragg grating (FBG) in a self-developed Yb-doped seven-core fiber using two femtosecond laser direct writing methods: a grating array inscription method and a plane-by-plane inscription method. The array fabrication method uses the femtosecond laser to directly write a parallel fiber grating array in the core. The plane-by-plane method is implemented by adding a diaphragm in the optical path to precisely control the length of the refractive index modulation line along the femtosecond laser incident direction. Combined with femtosecond laser scanning, a uniform refractive index modulation plane can be inscribed in the core in a single scanning. Based on these methods, we successfully fabricate high-quality high-reflection FBGs and chirped FBGs in each core of the large-core multicore fiber (MCF) with 14 μm core diameters. Both fabrication methods achieve FBGs with reflectivity above 97% at the central wavelength. We report for the first time the fabrication of high-quality, high-reflectivity FBGs in large-core Yb-doped seven-core fibers using the femtosecond laser plane-by-plane inscription method. This work provides a feasible scheme for fabricating FBGs in MCF.